Inactivation of Staphylococcus aureus and Enterococcus faecalis by a direct-current, cold atmospheric-pressure air plasma microjet() - Tian, Ye (Editorial Department of Journal of Biomedical Research, 2010)
OBJECTIVE: A direct-current, cold atmospheric-pressure air plasma microjet (PMJ) was performed to inactivate Staphylococcus aureus (S. aureus) and Enterococcus faecalis (E. faecalis) in air. The process of sterilization and morphology of bacteria was observed. We wish to know the possible inactivation mechanisms of PMJ and explore a potential application in dental and other temperature sensitive treatment. METHODS: In this study, we employed a direct current, atmospheric pressure, cold air PMJ to inactivate bacterias. Scanning electron microscopy was employed to evaluate the morphology of S. aureus and showed rupture of cell walls after the plasma treatment and Optical emission spectrum (OES) were used to understand the possible inactivation mechanisms of PMJ. RESULTS: The inactivation rates could reach 100% in 5 min. When the distance between the exit nozzle of the PMJ device and Petri dish was extended from 1 cm to 3 cm, effective inactivation was also observed with a similar inactivation curve. CONCLUSION: The inactivation of bacteria is attributed to the abundant reactive oxygen and nitrogen species, as well as ultroviolet radiation in the plasma. Different life spans and defensibilities of these killing agents may hold the key to understanding the different inactivation curves at different treatment distances.